Music Performance Pedagogy: Self-Regulation in Contrabass Practice - Hidayatullah, Riyan; Tejapermana, Prisma; Nikko Mazlan, Chamil Arkhasa (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2024)
This study explores instrumentalist (students) self-regulation in self-learning practices in a counter-bass class by integrating a performance pedagogy perspective. Self-regulation is the ability of individuals to regulate the learning process through planning, monitoring, and evaluating their performance (practice). This research uses a qualitative approach with a case study method. Data was collected through in-depth interviews, direct observation, and analysis of daily practice journals from students who took counter-bass classes at the college level. The results showed that effective self-regulation in counter-bass instrumentalists involves structured rehearsal planning, performance reflection, and artistic interpretation strategies aligned with pedagogical principles. This research makes a theoretical contribution to the development of self-regulation in the context of performance pedagogy by highlighting how self-directed learning strategies can be strengthened by integrating performative approaches. Implications of this research include incorporating elements of self-regulation and performance pedagogy into music education curricula, particularly on string instruments such as the contra-bass, which require a complex blend of technical and musical skills.